The Contribution of the Community Forest Program to the Income of the Lumban Lansang Forest Farmer Group, Siantar Utara Village, Parmaksian District, Toba Samosir Regency. - Perangin-Angin, Gita Perdamen; Nurul Qomar; Yulia Andriani (Jurnal Online Pertanian Tropik, 2022)
Community Forest is a state forest concession that is utilized and aimed at empowering and increasing the income of local communities by improving community welfare. North Siantar Village is a Community Forestry location in Toba Samosir district with the Lumban Lansang Forest Farmer Group (FFG) as the manager of the area. The purpose of this study was to analyze the contribution of Community Forest concessions to the income of Lumban Lansang FFG. This study uses observation and interview techniques with all members of the Lumban Lansang FFG (55 persons) to collect primary data which includes how to manage Community Forest by FFG, FFG knowledge of Community Forest, problems faced by FFG while managing Community Forest, and FFG income from Community Forest management. Documentation studies are obtained by studying several books, journals, the internet, and documents from related institutions. The analysis used to calculate the contribution of Community Forest is quantitative analysis and analysis of income from data that has been obtained in the field by adding up income from agricultural, non-agricultural activities, activities in Community Forest and other income. The results showed that the concession of Community Forest could contribute income to Lumban Lansang FFG of Rp. 269.950.000/year for all members of the Lumban Lansang FFG, and contributes to the total income which is 23.91%. Keywords: community forest, forest farmer group, income